2022
DOI: 10.3389/fimmu.2022.988121
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the intestinal microbiome to immune recovery after HCT

Abstract: Allogenic hematopoietic stem-cell transplantation (allo-HCT) is a curative-intent immunotherapy for high-risk hematological malignancies and immune deficiencies. Allo-HCT carries a high risk of treatment-related mortality (TRM), largely due to infection or graft-versus-host disease (GVHD). Robust immune recovery is essential for optimal patient outcomes, given the immunologic graft-versus-leukemia effect prevents relapse, and functional innate and adaptive immunity are both needed for the prevention and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…A limited number of studies have analyzed changes in the microbiota after surgical treatment for oncologic diseases ( Tong et al, 2020 ; Chen et al, 2022 ; Hajjar et al, 2023 ). Research has shown that the microbial community after surgery is similar to that of healthy individuals, which can promote the recovery of tumor patients ( Wolfe and Markey, 2022 ). A follow-up study found that changes in the gut microbiota can be considered potential biomarkers for tumor recurrence and can be used to stratify the risk of recurrence ( Peters et al, 2019 ; Huo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have analyzed changes in the microbiota after surgical treatment for oncologic diseases ( Tong et al, 2020 ; Chen et al, 2022 ; Hajjar et al, 2023 ). Research has shown that the microbial community after surgery is similar to that of healthy individuals, which can promote the recovery of tumor patients ( Wolfe and Markey, 2022 ). A follow-up study found that changes in the gut microbiota can be considered potential biomarkers for tumor recurrence and can be used to stratify the risk of recurrence ( Peters et al, 2019 ; Huo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this hypothesis, we observed a higher incidence of bacterial infections in the complement‐activated group, suggesting a higher use of antibiotics in this group that might have impacted the microbiota. Several studies have reported microbiota dysbiosis in patients undergoing HSCT characterized by a higher proportion of Enterococcus, Enterobacteriaceae, Clostridial bacteria, proteobacteria, and a decrease of Blautia Genus 46–49 . Patients with an important loss of microbiota diversity have a higher risk of NRM due to a high incidence of GI GVHD 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported microbiota dysbiosis in patients undergoing HSCT characterized by a higher proportion of Enterococcus, Enterobacteriaceae, Clostridial bacteria, proteobacteria, and a decrease of Blautia Genus. [46][47][48][49] Patients with an important loss of microbiota diversity have a higher risk of NRM due to a high incidence of GI GVHD. 47 Interestingly, bacteria-like Enterococcus can lead to the activation of classical complement pathway, 50 whereas other species, such as Enterobacteria, produce LPS and favors the complement lectin pathway activation.…”
Section: Endothelial Complications Infections and Complement Activationmentioning
confidence: 99%
“…Innate lymphocytes may recognize an increase in opportunistic gut pathogens and an intensification of gut pro-inflammatory responses ( Figure 2 ). Previous studies have demonstrated that opportunistic gut microbes, such as Enterococcus and Enterobacteriaceae , can modulate the immune response to vaccines by regulating the production of pro-inflammatory cytokines 50 . One study found that mice with a higher abundance of pro-inflammatory bacteria in their gut had a stronger immune response to vaccination than those with a lower abundance of pro-inflammatory bacteria 51 .…”
Section: Innate Lymphocytes May Recognize Increased Opportunistic Gut...mentioning
confidence: 99%